PID and inverse-model-based control of a twin rotor system - Toha, Siti Fauziah; Tokhi, Mohammad Osman (Cambridge University Press, 2011)
The use of active control techniques has intensified in various control applications, particularly in the field of aircraft systems. This paper presents an investigation into the control of rigid-body and flexible motion of a twin rotor multi-input multi-output system (TRMS) using intelligent inverse-model-based control schemes. The TRMS is an aerodynamic test rig representing the control challenges of modern air vehicle. The augmented feedback PID and feedforward inverse-model-based control has led to good tracking response and vibration reduction of the TRMS, with the use of particle swarm optimisation (PSO). As a comparison, methods using PID controllers are also presented. Experimental results are obtained using the test rig, confirming the viability and effectiveness of the proposed methodology as opposed to conventional PID controllers. The results and evidence from this method are justified, presented and discussed.